2020
DOI: 10.1177/0148558x20939720
|View full text |Cite
|
Sign up to set email alerts
|

Does IRS Monitoring Deter Managers From Committing Accounting Fraud?

Abstract: We examine whether monitoring by the Internal Revenue Service (IRS) affects managers’ decisions to engage in fraudulent financial reporting. We argue that IRS monitoring provides a disciplining effect reducing managements’ incentives to engage in rent diversion activities such as costly financial statement misreporting. Using information on IRS audit rates and instances of fraud disclosed in Securities and Exchange Commission (SEC) Accounting and Auditing Enforcement Releases (AAERs), we find evidence consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…The idea of auditing is often linked to irregularities or fraudulent financial statement (Mason and Williams, 2022; Afriyie et al , 2022). With the help of computer-assisted audit techniques, auditors’ works on detecting fraudulent financial statement become more efficient (Braun and Davis, 2003).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The idea of auditing is often linked to irregularities or fraudulent financial statement (Mason and Williams, 2022; Afriyie et al , 2022). With the help of computer-assisted audit techniques, auditors’ works on detecting fraudulent financial statement become more efficient (Braun and Davis, 2003).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…However, widespread frictions in the real capital market, such as information asymmetry and agency problems, lead to deviations from optimal investment decisions (Chen et al ., 2007; Jiang et al ., 2011). Existing studies have shown that tax enforcement can play a governing role (Dyck and Zingales, 2004; Desai et al ., 2007) in improving the quality of accounting information (Hanlon et al ., 2014; Mason and Williams, 2020) and reducing financing costs (Guedhami and Pittman, 2008; Ghoul et al ., 2011). Therefore, tax enforcement may affect the achievement of corporate investment goals.…”
Section: Introductionmentioning
confidence: 99%
“…First, it contributes to the tax enforcement literature by examining the impact of tax enforcement on corporate decision making. Existing studies mainly use developed capital markets as research targets to examine the impact of tax enforcement, including corporate tax avoidance (Hoopes et al ., 2012; Gupta and Lynch, 2016), corporate value (Desai et al ., 2007), capital cost (Guedhami and Pittman, 2008; Ghoul et al ., 2011), and accounting information quality (Hanlon et al ., 2014; Mason and Williams, 2020). The government plays an important role in China’s economic activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature shows that domestic and foreign institutional investors (Chen et al, 2007;Ferreira et al, 2010), short selling mechanisms (Chang et al, 2019), media coverage (Borochin & Cu, 2018), analyst coverage (Chen et al, 2015), external regulation by the SEC (Liu et al, 2021), and markets for corporate control (Masulis et al, 2007) Existing studies suggest that due to their tax claim on a firm's cash flow, tax authorities have the same incentives as shareholders to supervise insiders (management and controlling shareholders), and they do not face free-rider problems in preventing them from diverting resources for private benefit (Desai et al, 2007). Consequently, strengthening tax enforcement can improve financial reporting quality (Hanlon et al, 2014;Mason & Williams, 2022), reduce the cost of capital (El Ghoul et al, 2011;Guedhami & Pittman, 2008), and lower the probability of stock price crashes (Bauer et al, 2021).…”
mentioning
confidence: 99%